Analysis of the Development Model of the Russian Economy - Valery V. SMIRNOV; Vladislav L. SEMENOV; Anzhelika G. ABRAMOVA; Anna N. ZAKHAROVA; Tatyana A. LAVINA; Tamara V. TALANOVA; Nadezhda V. SEMENOVA (Communications of International Proceedings, 2021)
The article determines the development model of the Russian economy. As a result of the analysis of Russia’s movement in the “Doing Business” interstate corridor during the period 2006-2020, a significant change in the business environment from the level of developing countries to the level of developed countries has been singled out. The analysis of the indicators of the “Doing Business” movement in Russia for the period 2006-2020 has revealed priority areas – lending and liquidation of enterprises. The study has found that the growth of international reserves is comparable to the growth of RTI; RGBI – within the growth range from foreign exchange reserves to the growth of monetary gold; reserve position in the IMF – with IMOEX. In the Russian model of economic development, the financial and oil and gas sectors are singled out, which significantly affect the business environment. The study sets the priority “Public administration and military security; social security”, indirectly implemented through “Product taxes/Net product taxes”. The contradictory position regarding favorable business conditions and the results of economic activity determine the actual model of development of the Russian economy.
Keywords: Model; Development; Doing Business; Innovation; Concept; Growth Rates.